2009
DOI: 10.1111/j.1365-2265.2009.03751.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune function in hypopituitarism: time to reconsider?

Abstract: Hypopituitarism is not currently considered as a potential cause of immune disruption in humans. Accumulating data from in vitro and animal models support a role for the pituitary gland in immune regulation. Furthermore, the increased mortality risk noted in patients with adult hypopituitarism remains poorly explained and immune dysfunction could conceivably contribute to this observation. In a recent issue of Clinical & Experimental Immunology, we presented new data relating to immune status in adults with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 82 publications
3
7
0
Order By: Relevance
“…These findings support the hypothetical contribution of the neuroendocrine axis to innate immunity, as recently suggested in human severe hypopituitarism [31]. Other pituitary hormones such as GH, corticotropin and prolactin, but not gonadotropins, have also been identified as potential candidate hormone mediators of disruption of immune homoeostasis in these patients [31]. Other pituitary hormones such as GH, corticotropin and prolactin, but not gonadotropins, have also been identified as potential candidate hormone mediators of disruption of immune homoeostasis in these patients [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings support the hypothetical contribution of the neuroendocrine axis to innate immunity, as recently suggested in human severe hypopituitarism [31]. Other pituitary hormones such as GH, corticotropin and prolactin, but not gonadotropins, have also been identified as potential candidate hormone mediators of disruption of immune homoeostasis in these patients [31]. Other pituitary hormones such as GH, corticotropin and prolactin, but not gonadotropins, have also been identified as potential candidate hormone mediators of disruption of immune homoeostasis in these patients [31].…”
Section: Discussionsupporting
confidence: 90%
“…These findings support the hypothetical contribution of the neuroendocrine axis to innate immunity, as recently suggested in human severe hypopituitarism [31]. These findings support the hypothetical contribution of the neuroendocrine axis to innate immunity, as recently suggested in human severe hypopituitarism [31].…”
Section: Discussionsupporting
confidence: 90%
“…In these studies, GH treatment has been found to diminish Fas-mediated cell death via increasing the expression of Bcl-2 and inhibiting the activation of caspase 3 [38] and to protect lymphocytes from irradiation- [39] and methyl methanesulfonate- [40] induced cell death. Several excellent reviews summarize the various effects of GH on immune cells and function [23-27; 41-44]. …”
Section: Growth Hormonementioning
confidence: 99%
“…The vast majority of clinical and experimental studies have focused on stages with increased inflammation where it seems that chronic inflammation suppresses the GH/IGF1 axis (2,5,6,7,8,9). In addition, more recent observations have demonstrated that the relationship may be bidirectional, with GH/IGF1 activity influencing inflammatory processes (3,10,11). However, the association seems complicated as data obtained from in vivo and in vitro studies have been supporting pro-inflammatory (3,12,13) as well as anti-inflammatory effects of GH and IGF1 (3,13,14,15).…”
Section: Introductionmentioning
confidence: 99%